2019
DOI: 10.3389/fmicb.2019.02137
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Enzyme Activity and Its Implications for Organic Matter Cycling in Northern Chinese Marginal Seas

Abstract: Extracellular enzymes, initiating the degradation of organic macromolecules, are important functional components of marine ecosystems. Measuring in situ seawater extracellular enzyme activity (EEA) can provide fundamental information for understanding the biogeochemical cycling of organic matter in the ocean. Here we investigate the patterns of EEA and the major factors affecting the seawater EEA of Chinese marginal seas. The geographic distribution of EEA along a latitudinal transect was examined and found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 72 publications
(105 reference statements)
1
12
0
Order By: Relevance
“…Five extracellular enzymes including protease, lipase, urease, α-glucosidase, and phosphatase were produced by A. limacinum BUCHAXM 122, consistent with previous reports for other species of Aurantiochytrium [23,34] and also for Shizochytrium and Thraustochytrium [34]. Similar to the ecosystem in which A. limacinum is found, phosphatase, βglucosidase and protease are also found in the bacteria such as Planctomycetes, Chloroflexi, Roseobacter, Alteromonas and Pseudoalteromonas [35]. However, most bacteria that live in seawater, sediment, plants and animals produce lipase phosphatase and protease, and a few produce urease [36].…”
Section: Discussionsupporting
confidence: 87%
“…Five extracellular enzymes including protease, lipase, urease, α-glucosidase, and phosphatase were produced by A. limacinum BUCHAXM 122, consistent with previous reports for other species of Aurantiochytrium [23,34] and also for Shizochytrium and Thraustochytrium [34]. Similar to the ecosystem in which A. limacinum is found, phosphatase, βglucosidase and protease are also found in the bacteria such as Planctomycetes, Chloroflexi, Roseobacter, Alteromonas and Pseudoalteromonas [35]. However, most bacteria that live in seawater, sediment, plants and animals produce lipase phosphatase and protease, and a few produce urease [36].…”
Section: Discussionsupporting
confidence: 87%
“…These results point to possible contributions of microbial metabolites such as organic acids or extracellular enzymes to MAOM mobilization. Both have recently been implicated in the release of MAOM, either through the displacement of weakly bound compounds or enzymatic hydrolysis of surface-bound polymers. , A recent study showed that ectomycorrhizal fungi growing in media facilitated the mobilization of polymeric MAOM from goethite. MAOM mobilization was attributed to the interplay of fungal metabolites coating the surfaces and extracellular enzymes depolymerizing complex MAOM, bypassing the desorption step .…”
Section: Discussionmentioning
confidence: 99%
“…At all sites, similar proportions of taxa were recorded. At the phylum level they were represented by Bacterioidetes, Proteobacteria and Actinobacteria (Figure 5), which have the ability to produce a variety of extracellular enzymes and have been identified as dominant bacterial taxa in both marine [57] and riverine [30] environments. With more than 18% share in the total microbial community in the middle river course, Flavobacterium dominated at the genus level (Figure 6).…”
Section: Discussionmentioning
confidence: 99%